DIKOTOMI ULAMA` MENURUT AL-GHAZALI (KLASIFIKASI ULAMA AL-DUNYA DAN ULAMA AL-AKHIRAT) - Maftuh Maftuh (Institut Keislaman Abdullah Faqih Gresik, 2016)
Abstrak: This article will discuss the ulama' dichotomy according to al-Ghazali. This paper begins with a discussion of the biography of al-Ghazali. Then the author will try to analyze various matters concerning al-Ghazali in explaining the dichotomy and the criteria of the ulama', why and what factors are behind the thought of al-Ghazali? or other issues that are really needed to be discussed in the author's view. Based on the description and analysis of the dichotomy of ulama according to al-Ghazali, it can be concluded that, the initial statement is to discuss the role and characteristics of the dichotomy of ulama, namely ulama' dunya or ulama su' and ulama al-akhirat. Problems that arose related to the role of the ulama at that time, al-Ghazali gave a criticism, because at that time the main role of the ulama' had shifted a lot towards power by looking for worldly interests, thus forgetting the main role that should be a big responsibility that must have. In addition, he also wanted to know the extent of the shift and orientation of the ulama in their role at that time. Keyword: ulama' dichotomy, al-Ghazali, ulama' dunya, ulama, ulama al-akhirat